A bibliometric study on SCRUM approach: patterns, trends and gaps - Antônio Carlos Bonassa; Marly Monteiro de Carvalho (GEPROS: Gestão da Produção, Operações e Sistemas, 2016)
After Agile Manifesto success in the software development arena, the literature on Agile methods, particularly SCRUM has increased. This study aims to present a systematic literature review of SCRUM literature, identifying the main evolution patterns, trends, and gaps. The research methods combine the bibliometric approach with content analysis. The results show that despite the increase interesting on agile methods, SCRUM utilization is decreasing and/or being replaced by another project management method and it face so strong barriers to expanding in other sectors than software. The main advantages of applying SCRUM pointed out in the review are increase customer satisfaction at the same time that reduced associated costs and development time.